Artificial aeration promotes better zootechnical performance and physiological balance of tambaqui (Colossoma macropomum) cultivated in a system without continuous water flow (Amazon: Brazil) (Research, Society and Development, 2021)
The aimed of the study was to evaluate the effect of continuous artificial aeration on zootechnical performance, hematological characteristics and glucose concentration of tambaqui (Colossoma macropomum) cultivated in a system without water flow. The study was conducted with two treatments, with aeration and without artificial aeration. Were 600 tambaqui juveniles with an average initial weight of 15 ± 0.15g were distributed in two excavated tanks. Thirty fish were captured per cultivation unit to perform monthly biometric measurements and were subjected to blood collection to determine hematological parameters. There was no difference between hematological variables (p